Engineering Classes as a Tool of Professional Navigation - O. N. Vasilieva; N. V. Konovalova (Moscow Polytechnic University, 2019)
The article emphasizes the importance and relevance of engineering education in the face of challenges of the modern information society, development of new technologies and knowledgeintensive industries. Attention is paid to the low level of demand for engineering professions among potential entrants, as well as to the issue of developing competencies needed for a modern engineer, taking into account the requirements of the labour market. The article describes the experience of I.N. Ulianov Chuvash State University on organizing career-guidance work with pupils of educational in-stitutions, including implementation of projects aimed at popularization of engineering education. One of such significant for the region projects is "Engineering classes", in which senior classes schoolchildren of four leading partner-schools of the University take part. The training program includes lessons on mathematics, physics and computer sciences, reinforcing training of future entrants for getting higher engineering-technical education, as well as an elective part on solving applied engineering tasks from the following sections: electronics, robotics, mechatronics, 3D modeling, engineering graphics, and prototyping. A specific feature of the project is a broad engagement of students majoring in technical directions as tutors into the educational process when schoolchildren perform research and design work. Along with higher levels of knowledge in basic subjects for a future engineer, an active participation of schoolchildren in project activities makes it possible to develop communication skills, acquire experience of team work, which is particularly in demand by employers. The article stresses the important role of the largest industrial regional enterprises in implementing the project. These enterprises provide their production sites to explore the organization of production and professional activities of engineers, as well as participate in holding Olympiads and creative contests and provide opportunities for subsequent target training. Thus, the project «Engineering classes» makes it possible to implement the model of continuing education in a single chain «School-University-Enterprise», thereby creating preconditions for the growth of human capacity in regional high-tech enterprises.